The death of Yasser Arafat: molecular-genetic authentication of the remains as an indispensable condition for the evaluation of the medical hypotheses of the cause of his death - Zemskova, E Yu; Kvacheva, Yu E; Kovalev, A V; Ivanov, P L (Sudebno-meditsinskaia ekspertiza, 2015)
The objective of the present study was the molecular-genetic authentication of the remains as an indispensable condition for the evaluation of the medical hypotheses of the cause of death in 2004 of Yasser Arafat, the former Palestinian leader and the first president of the Palestinian National Administration, the Nobel Peace Prize laureate. We carried out molecular-genetic investigations aimed at establishing the circumstances and cause of the death of Yasser Arafat including the analysis of the relevant medical documentation, the examination of the burial place at Ramallah, remains, and personal belongings stored in his Al Muqata'ah residence at Ramallah. The objective of the present molecular- genetic investigations was to confirm the authenticity of the fragments of Yasser Arafat's remains available for radio-toxicological, chemical toxicological, and other laboratory studies. The reference objects were the contact traces left on the personal belongings by their owner. The aggregate probabilistic estimate of the coincidence of genotype traits of autosomal DNA, Y-chromosomal DNA, and mtDNA was at least 99,(9)29 4% which gives evidence of the genetic identity of the objects of study. It is this value (99.999999 <...> 9999999(29) 4%) that characterizes the probability that the bone fragments provided for the laboratory studies are actually authentic remains of Yasser Arafat.